THE IMPLEMENTATION OF FINTECH IMPLEMENTATION ON FINANCIAL INCLUSION IN EAST KALIMANTAN, INDONESIA - La Ode Hasiara; Fatahul Rahman; Zul Fikar; Dimas Syahputra (International Journal of Social Science, 2025)
The objective of this study is to identify, analyze, and explain the types of fintech technology, financial education and literacy, ease of access and use, fintech education programs, and access to financial services that have both direct and indirect effects on financial inclusion in Indonesia. This research employs a quantitative approach using the Partial Least Squares (PLS-SEM) model. The sampling technique used is purposive sampling based on specific predetermined criteria. The total number of respondents in this study is 697. The findings indicate that four variables fintech technology, financial education and literacy, ease of access and use, and fintech education programs have a positive and significant direct effect on access to financial services. Furthermore, five variables fintech technology, financial education and literacy, ease of access and use, fintech education programs, and access to financial services have a positive and significant direct effect on financial inclusion in Indonesia. Additionally, four variables fintech technology, financial education and literacy, ease of access and use, and fintech education programs have a positive and significant indirect effect on financial inclusion in Indonesia